Purchase, pirate, publicize: The effect of file sharing on album sales - Jonathan Lee (Queen's University, Department of Economics, 2016)
This paper quantifies the relationship between private-network file sharing activity and music sales in the BitTorrent era. Using a panel dataset of 2,251 albums' U.S. sales and file sharing downloads on a private network during 2008, I estimate the effect of file sharing on album sales. Exogenous shocks to file sharing capacity address the simultaneity problem. In theory, piracy could crowd out legitimate sales by building file sharing capacity, but could also increase sales through word-of-mouth. I find evidence that additional file sharing decreases physical sales but increases digital sales for top-tier artists, though the effects are modest. I also find that file sharing may help mid-tier artists and substantially harms bottom-tier artists, suggesting that file sharing enables consumers to better discern quality among lesser-known artists.
Keywords: L82; L86; O34; 330; intellectual property; copyright; file sharing; piracy; digital music